Public Service Innovation through ARSI (Study in Rampal Celaket Village) - Yustina Ndung; Maria Alvelita Reong Loli (University of Merdeka Malang, 2023)
The public's demand for public service has encouraged the government to innovate services to improve public service. One service that must be considered is the service of incapacity certificate. The purpose of this study is to describe and analyze the service of a certificate of incapacity through ARSI in Rampal Celaket Village. This type of research uses a qualitative approach. Data was collected through interviews, observation, and documentation with a research focus on online service ARSI, management of incapacitated certificates, and Certificate of Disadvantage service procedures consisting of indicators of the simplicity of service procedures, clarity of service, ease of service access, and timeline in service. The result of the study shows that the certificate service for incapacity through ARSI is implemented in the Rampal Celaket Village based on the principle of public service according to the Minister of Administrative Reform No. 63 of 2003 concerning General Guidelines for the Implementation of Public Services. The Rampal Celaket Sub-District Office is making efforts to simplify service procedures seen from access via WhatsApp besides seeking clarity of service seen from the ARSI service display which contains various information about the Rampal Celaket Village in detail, then ease of service through ARSI seen from access via cellphone and how to use it by clicking or typing according to needs and supported by supporting facilities and infrastructure as well as the ability of employees.